Replication Data for: Database of Occurrence and characterization of insect galls in two reserves of the Peruvian Amazon - Grandez Rios, Julio Miguel (2024)
The present dataset contains characterizations of the external morphology of gall insects in the Allpahuayo-Mishana National Reserve and Quistococha Regional Reserve within four vegetation types: terra firme forest, white-sand wet forest, white-sand dry forest, and palm swamp forest. The purpose of this database is to facilitate access to this information and serve as an incentive for individuals interested in studying the diversity of gall-inducing insects in the Amazon forest.